Artistic anti-counterfeiting with a pH-responsive fluorescent ink using DFT and molecular electrostatic potential mapping insights - Hebat-Allah S. Tohamy (Scientific Reports)
Abstract The observed fluorescence behavior of the sulfur, nitrogen-doped carbon dots (S, N-CDs) ink which derived from onion peel wastes (OW) demonstrates its pH-sensitive nature, making it suitable for applications where visual or fluorescent changes upon pH variation are desired. The initial lack of fluorescence under UV light suggests that the S, N-CDs in the ink are in a non-fluorescent state. However, upon treatment with acid, the ink exhibits a faint yellow color under light and fluoresces under UV light. This indicates a shift in the electronic structure of the S, N-CDs, likely due to protonation. The return to non-fluorescence after re-treatment with alkaline solution suggests that the de-protonation process reverses the effect of acid, restoring the S, N-CDs to their original non-fluorescent state. This reversible pH-sensitivity is a valuable asset for various applications. The synthesized S, N-CDs exhibited a reversible change in fluorescence intensity under acidic and alkaline conditions, transitioning from non-fluorescent to fluorescent under acidic conditions and back to non-fluorescent in alkaline media. Density Functional Theory (DFT) calculations revealed that S, N-doping resulted in a narrower energy gap (0.2779 eV compared to 0.3199 eV for N-CDs) and a higher dipole moment (2.640 Debye), enhancing their reactivity towards protons and leading to more pronounced color and fluorescence changes across different pH conditions. The S, N-CDs displayed dual fluorescence emission peaks at 443.00 nm and 502.00 nm upon excitation at 350 nm, and fluorescence contour maps (FCM) confirmed their multicolor emission capabilities. The calculated quantum yield for the S, N-CDs was notably high at 37.76%. Fourier Transform Infrared (FTIR) spectroscopy confirmed the successful incorporation of sulfur (S–H at 2368 cm⁻1, C–S at 750 cm⁻1) and nitrogen (N–H at 3552 cm⁻1, C–N at 989 cm⁻1) functionalities into the carbon dot structure. Furthermore, Molecular Electrostatic Potential (ESPM) mapping indicated regions of high negative potential around S, OH, and C=O groups, particularly pronounced under acidic and basic conditions, supporting the observed pH sensitivity.